Saying Their Names: Prayers Prayed by the Elderly - Doud, Robert E. (The way, 2025)
The article explores the spiritual practices and reflections of elderly Catholics, highlighting the role of prayer, Mass, and gratitude in daily life. It describes a home Mass on All Souls' Day in 2024, including a ritual called "Say Their Names," where participants remembered deceased loved ones and notable figures such as Maggie Smith, Fernando Valenzuela, and Gustavo Guttiérez, emphasizing the enduring presence of Jesus in everyday worship.